Miniature eye movements enhance fine spatial detail - Rucci, Michele; Iovin, Ramon; Poletti, Martina; Santini, Fabrizio (Nature, 2007)
An eye for detail The function of fixational eye movements, the tiny involuntary eye movements or 'retinal jitters' that occur when we fix our gaze on something, has been a matter of debate since they were first recognized in the 1950s. Using a combination of psychophysical experiments with statistical analysis of the visual signals entering the eye to counteract the visual effects of the eye movements, Rucci et al . show that without them, perception of fine-grained information is reduced. This suggests that fixational eye movements are part of a strategy used by the brain to extract fine details of visual information. Our eyes are constantly in motion. Even during visual fixation, small eye movements continually jitter the location of gaze 1 , 2 , 3 , 4 . It is known that visual percepts tend to fade when retinal image motion is eliminated in the laboratory 5 , 6 , 7 , 8 , 9 . However, it has long been debated whether, during natural viewing, fixational eye movements have functions in addition to preventing the visual scene from fading 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 . In this study, we analysed the influence in humans of fixational eye movements on the discrimination of gratings masked by noise that has a power spectrum similar to that of natural images. Using a new method of retinal image stabilization 18 , we selectively eliminated the motion of the retinal image that normally occurs during the intersaccadic intervals of visual fixation. Here we show that fixational eye movements improve discrimination of high spatial frequency stimuli, but not of low spatial frequency stimuli. This improvement originates from the temporal modulations introduced by fixational eye movements in the visual input to the retina, which emphasize the high spatial frequency harmonics of the stimulus. In a natural visual world dominated by low spatial frequencies, fixational eye movements appear to constitute an effective sampling strategy by which the visual system enhances the processing of spatial detail.